Uxoricide related to folie a deux: Apropos of a case - Villanueva Salas, Oscar (2024)
Introduction: From the etymological point of view, uxoricide comes from two Latin words: uxor, meaning spouse, and caedere (cide), meaning the housewife is killed by her husband. Clinical case: This is a case of an expert assessment of a patient who probably had schizophrenic psychosis, who was killed by her husband. We emphasize the importance of personality traits in the passage of this mental condition to another person, and the degree of involvement is related with being so close to the primarily affected person.